Analisis Strategi Kesiapan Dinas Pariwisata Kota Padang Dalam Menyelenggarakan Wisata Halal - Aditya Adila; Yulhendri Yulhendri (Universitas Negeri Padang, 2022)
This study aims to determine the readiness of Padang City Tourism Office in organizing halal tourism and to determine the strategy for developing halal tourism by the Padang Citu Tourism Office using a SWOT analysis. This type of research is a qualitative research using a descriptive approach with the research subject of employees of the Padang City Tourism Office. Data was collected through observation, interviews and documentation. Testing the validity of data using the triangulation technique and for the description of the data using the SWOT analysis technique. The results of the study indicate that the Padang City Tourism Office is still not ready to organize halal tourism. The Padang City Tourism Offie does not yet have official regulations regarding the implementation of halal tourism. But so far the Padang City Tourism Office has made efforts to accelerate the implementation of halal tourism in Padang City. Based on the result of the SWOT analysis, there are several strategies for developing halal tourism. The main strategy that can be carried out by the Padang City Tourism Office is to provide assistance and convenience for business actors who want to take care of halal certification.